Basic chemistry - Malone, Leo J.; Dolter, Theodore O.; Gentemann, Steven (Singapore : John Wiley & Sons, 2013)
Basic concepts of chemistry will provide the necessary forum for students to master fundamental problem solving skills, through the framework of outcomes assessment.
International student version.
Includes index.
Keywords: Chemistry; Physical sciences